Nutrition and Diet Therapy, 10th Edition - Linda Kelly DeBruyne; Kathryn Pinna; Eleanor Noss Whitney (Cengage Learning, 2019)
Low carb, low-fat, high protein, sugar-free. How can you help others eat right when popular diets offer conflicting advice? NUTRITION AND DIET THERAPY, 10th Edition, delivers solid nutritional guidance without fads and hype. Based on scientifically supported concepts and clinical approaches, this book prepares you to assess nutritional needs in clients with varying health concerns, create focused diet plans and set realistic nutritional goals. Even better, content is designed logically around diet types, rather than diseases and organs, to jump-start your success in any role on any health care team. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.